Electrical impedance tomography as possible guidance for individual positioning of patients with multiple lung injury. (6th May 2016) - Lehmann, Sylvia; Leonhardt, Steffen; Ngo, Chuong; Bergmann, Lukas; Schrading, Simone; Heimann, Konrad; Wagner, Norbert; Tenbrock, Klaus
Abstract: Introduction: Electrical Impedance Tomography (EIT) is a tomographic, radiation‐free technique based on the injection of a harmless alternating current. Objective: As electrical impedance strictly correlates with the variation of air content, EIT delivers highly dynamic information about global and regional ventilation. We want to demonstrate the potential of EIT individualizing ventilation by positioning. Methods: Gravity‐dependent EIT findings were analyzed retrospectively in a critically ill mechanically ventilated pediatric patient with cystic fibrosis and coincident lung diseases. To further evaluate gravity‐dependent changes in ventilation, six adult healthy and spontaneously breathing volunteers were investigated during simultaneous detection of EIT, breathing patterns, tidal volume (VT) and breathing frequency (BF). Results: EIT findings in healthy lungs in five positions showed gravity‐dependent effects of ventilation with overall ventilation of predominantly the right lung (except during left‐side positioning) and with the ventral lung in supine, prone and upright position. These EIT‐derived observations are in line with pathophysiological mechanisms and earlier EIT studies. Unexpectedly, the patient with cystic fibrosis and lobectomy of the right upper and middle lobe one year earlier, showed improvement of global and regional ventilation in the right position despite reduced lung volume and overinflation of this side. This resulted in individualized positioning and improvement of ventilation. Conclusions: Although therapeutic recommendations are available for gravitational influences of lung ventilation, they can be contradictory depending on the underlying lung disease. EIT has the potential to guide therapists in the positioning of patients according to their individual condition and disease, especially in case of multiple lung injury.